2017
DOI: 10.1097/md.0000000000007853
|View full text |Cite
|
Sign up to set email alerts
|

Nonalcoholic fatty liver was associated with asymptomatic gallstones in a Chinese population

Abstract: The aim of this study was to determine the association between nonalcoholic fatty liver disease (NAFLD) and asymptomatic gallstones in a Chinese population.The study had a cross-sectional design and enrolled 7583 subjects who visited the physical check-up center at Sir Run Run Shaw Hospital between 2009 and 2011. Colorimetric methods were used to measure the levels of cholesterol, high-density lipoprotein cholesterol (HDL-C), and low-density lipoprotein cholesterol (LDL-C), whereas fasting plasma glucose (FPG)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 39 publications
3
18
0
Order By: Relevance
“…Most of their GSD patients were female, which was similar to our study and may be due to differences in sex hormones and cholesterol metabolism in women. 38 A cross-sectional study of 7,583 Chinese subjects showed that asymptomatic gallstones are strongly associated with NAFLD in this population, 37 which is consistent with our study. Another study of the Chinese population concluded that NAFLD is associated with GSD in an urban population of middle and upper socioeconomic strata.…”
Section: Gsdsupporting
confidence: 90%
See 1 more Smart Citation
“…Most of their GSD patients were female, which was similar to our study and may be due to differences in sex hormones and cholesterol metabolism in women. 38 A cross-sectional study of 7,583 Chinese subjects showed that asymptomatic gallstones are strongly associated with NAFLD in this population, 37 which is consistent with our study. Another study of the Chinese population concluded that NAFLD is associated with GSD in an urban population of middle and upper socioeconomic strata.…”
Section: Gsdsupporting
confidence: 90%
“…Although a few previous studies have shown that the overall prevalence of GSD in patients with NAFLD is not significantly different from those with non-NAFLD, 33 many recent studies suggest a significant association between them. 17,18,[34][35][36][37][38] In our study, there was significant association between GSD and NAFLD (Table 6). NAFLD was present in 62% of GSD patients in one observational study by Ahmed et al, 38 which was higher than our report (42.4%), also the level of LFT in their patients was higher in the NAFLD group, which was similar to our study ( Table 5).…”
Section: Gsdsupporting
confidence: 58%
“…Previous studies, which have included mostly cross-sectional studies and only a few cohort studies, have evaluated the association between NAFLD and GD, but their relationship remains controversial [ 38 , 39 , 40 ]. While some of these cross-sectional studies showed an increased prevalence of GD in patients with NAFLD, others reported a relationship in the other direction, showing an increased prevalence of NAFLD in patients with GD or cholecystectomy [ 13 , 14 , 15 , 16 , 38 , 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have identified modifiable risk factors for GD, including NAFLD and metabolic syndrome. [7,14] Recently, an association between GD and NAFLD has been reported in a Chinese population [15] ; however, an association between grade of NAFLD and GD could not be determined. This study aimed to determine whether NAFLD grade is an independent risk factor for GD in a Korean population.…”
Section: Introductionmentioning
confidence: 99%